Ectoparasite Infestation Prevalence in Cats (Felis Domestica) at the Teaching Animal Hospital of FKH IPB - Tetty Barunawati Siagian; Eka Rahmadhani Siregar (UNIVERSITAS ISLAM LAMONGAN, 2021)
Cats are animals that are widely kept by the people of Indonesia. Both domesticated and feral cats can be attacked by ectoparasites. Ectoparasites that attacks cats are ticks, mites, fleas and fleas. Ectoparasites can breed well if the sanitation and cleanliness of the cat's cage is not maintained. Data collection was carried out for one month from February 1st - 28th Â 2021 .Ectoparasite samples were taken directly from every cat that came to RSHP. The results of the examination showed that 27 cats were positively infected with ectoparasites from 29 cats that had the potential to be infected with ectoparasites. The prevalence of ectoparasite infestation in domestic cats that came to RSHP was 93,1%. A total of 27 cats were infested with ectoparasites consisting of 2 Rhipicephalus sanguineus fleas, 11 Felicola subrostratus fleas, two Sarcoptes scabiei infection mites, 14 infectious mites Otodectes cynotis and infection mites. Ctenocephalides felis as many as 7 tails. One individual cat may be more affected than one type of ectoparasite. The calculation of the prevalence of ectoparasites in cats observed was 93,1%, which consisted of the prevalence of Sarcoptes scabiei infestation 6,89%, Otodectes cynotis 48,27%, Ctenocephalides felis 24,13%, Ripicephalus sanguineus 6,89% and Felicola subrostratus 37,93 %. The presence of ectoparasites can be minimized by always maintaining cleanliness and routine caring for cats.